Formulate credible approaches to fight poverty in pandemic age - Jamaiudin, Norhaslinda (New Straits Times Press (M) Bhd., 2021)
This writing is based on my brief analysis on the multidimensionally poor households in Malaysian and the need for the government to revise the approach and develop more credible strategies through a multidimensional poverty framework.